Cultivo de arroz de terras altas submetido à adubação silicatada e tensões de água no solo - Oliveira, Jakeline Rosa de (2014)
Rice cultivation of upland in Brazil occurs mainly in the Cerrado area, region with adverse weather conditions. Therefore the use of silicon in cultivation becomes important for increasing the crop yield, since it provides regulation of evaporation, improved leaf architecture and a reduction in disease incidence. Thus aimed to evaluate the effect of silicon fertilization and soil water tensions in the cultivation of upland rice in the Cerrado Oxisol. The experiment was conducted in a greenhouse. The soil was collected from an area of Cerrado vegetation. Was used 5x5 factorial fractional design with five tensions water in soil (0, 15, 30, 45 and 60 kPa) and silicon five doses (0, 120, 240, 480 and 960 mg dm-3) which were distributed according to the statistical design of randomized blocks with four replications. Each experimental plot consisted of a pot of 8 dm -3 the one tensiometer installed at a depth of 13 cm. The following characteristics were evaluated: leaf angle, chlorophyll index, plant height, flowering, number of tillers, number of leaves, number of panicle, panicle length, number of grains per panicle, percentage of empty grains, grain weight, dry weight of shoot and root dry mass, concentration and accumulation of silicon. Results were submitted to statistical analysis using the SAS statistical program. Silicon fertilization improved architecture of rice plants with reduced leaf angle and increased chlorophyll content in silicon doses of 785 and 750 mg dm-3, respectively. The 45 kPa water tension promoted reduction in the aerial part dry weight, dry weight of roots, concentration and silicon accumulation in upland rice plants. The increase in water tension in the soil reduced the yield of upland rice grown in culture pot in Cerrado Oxisol.